DEVELOPMENT OF CONTINGENCY-BASED ENTERPRISE EXCELLENCE INDEX CRITERIA USING ANALYTIC NETWORK PROCESS - Sulistyo, B.; Mohammad, M.; Safian, E.E.M. (Journal of Advanced Manufacturing Technology (JAMT), 2024)
Business Excellence Models (BEMs), such as the Baldrige Excellence Framework (BEF), provide comprehensive frameworks for assessment and guidance towards achieving organisational excellence. However, generic and cultural misalignment of BEF can limit its effectiveness in addressing the distinctive circumstances of the enterprises. This study addresses this gap by developing the Enterprise Excellence Index (EEI) criteria tailored for Indonesian State-Owned Enterprises (SOEs), adapting from the BEF. Moreover, the existing calculation method used has the limitation of not taking into consideration the interdependence of the criteria. Instead, in this study, the Analytic Network Process (ANP) is applied since it allows for more complicated interrelationships and could prioritise groupings or clusters of elements in a nonlinear and non-hierarchical structure. The final result of the EEI shows a different composition compared to the BEF in Categories 3, 4, 5, and 7. While the scores for each category and the total score of both frameworks remain the same, there is no different score composition in Categories 1, 2, and 6. Meanwhile, the difference between the EEI and Category 7 is in composition and the total score for each item. The EEI is also compared to the Malaysia Business Excellence Framework (MBEF), which shows a total difference in all categories and item scores.